The Role of Iran and America's Middle East Policy in Peace Process of Middle East 2001-2016 - Jalalpoor, Shiva; Sharfi, Hadi (Journal of History Culture and Art Research, 2017)
Abstract The Middle East peace process has become the most important international Middle Eastern politics phenomenon during the recent decades. Since the U.S. has realized the political, military and economic power of Iran and its influence as peace building in the Middle East, diplomacy with a common approach on the agenda has developed between these two countries. Therefore, the purpose of this study is to investigate American and Iranian role in the Middle East and diplomatic relations between the two countries in the process of establishing peace in the region. The main question in the present research is that; what is the role of American and Iranian Middle East policy in the peace process in the Middle East during 2001-2016? To response to the question, a descriptive—analytical approach is implemented. The results suggest that the lack of diplomatic relations between Iran and America in the years 2001-2016 is one of the main reasons of the lack of security and peace in the Middle East. Accordingly, creating opportunities and establishing diplomatic relations (political, economic, social, and etc.) between Iran and America with the interests of the two countries as the two poles of influence in all parts of the region, not only provides security, but also is an indicator to stabilize discipline and a lasting peace in the region. Last but not least, communication between Iran and the U.S. ensures safety of the region.